1998
DOI: 10.1210/jcem.83.3.4649
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Estrogen Receptor Allelic Variants in Italian Postmenopausal Women: Evidence of Multiple Gene Contribution to Bone Mineral Density

Abstract: Bone mass and bone turnover are under genetic control. Restriction fragment length polymorphisms (RFLPs) at the vitamin D receptor (VDR) gene locus have been recently correlated to bone mineral density (BMD) and rate of bone loss. However, agreement on this relationship is not universal. The existence of ethnical and environmental differences between populations, a health-based selection bias in several previous studies, and the involvement of other genes could explain these discordant findings. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
63
2
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 31 publications
8
63
2
3
Order By: Relevance
“…For example, the VDR knockout mouse displays critical growth defects in the female reproductive organs, speci®cally hypoplasia of the uterus, partly attributable to a lack of estrogen production, thus further supporting a role for VDR in the regulation of estrogenic events (Yoshizawa et al, 1997). Similarly, speci®c VDR and ER polymorphisms are linked to bone mineral density in postmenopausal women (Gennari et al, 1998;Deng et al, 1998) and to the regulation of infant growth (Suarez et al, 1998). Also, VDR polymorphisms are associated with increased risk for prostate cancer and the progression of breast cancer, possible as a result of altered transcriptional activity (Ingles et al, 1997;Lundin et al, 1999;Jurutka et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…For example, the VDR knockout mouse displays critical growth defects in the female reproductive organs, speci®cally hypoplasia of the uterus, partly attributable to a lack of estrogen production, thus further supporting a role for VDR in the regulation of estrogenic events (Yoshizawa et al, 1997). Similarly, speci®c VDR and ER polymorphisms are linked to bone mineral density in postmenopausal women (Gennari et al, 1998;Deng et al, 1998) and to the regulation of infant growth (Suarez et al, 1998). Also, VDR polymorphisms are associated with increased risk for prostate cancer and the progression of breast cancer, possible as a result of altered transcriptional activity (Ingles et al, 1997;Lundin et al, 1999;Jurutka et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…These same 2 SNP have also been associated with other estrogen-linked conditions, 22,23 as well as factors associated with increased breast cancer risk, such as age at menopause 24 and age at menarche. 25 In addition, increased bone mineral density, a potential surrogate marker of cumulative estrogen exposure and a predictor of breast cancer risk, 26 has also been associated with these SNP, 27,28 although not consistently. 29 These data suggest that the ESR1 2401 T/C and 2354 A/G polymorphisms may act as susceptibility or risk-modifying alleles for breast cancer.…”
mentioning
confidence: 99%
“…Restriction fragment length polymorphisms (RFLPs) for a PvuII and a XbaI restriction site in intron 1 have also been associated with alterations in BMD. Different populations of European origin 11,12 show very similar allele frequencies at these loci, in contrast to oriental and Japanese populations, 13 which show markedly different allele fre-quencies. Consequently, although studies on both groups have shown gene associations with BMD, direct comparisons are difficult to make, and it has been suggested that some of these genetic associations may be population specific.…”
mentioning
confidence: 90%
“…7 The oestrogen receptors are also involved in a wide range of biological responses, including repression of the inflammatory response. 8 Gene polymorphisms have been reported for both ERa and ERb genes, and associations have been reported between specific ER alleles and a number of biological characteristics, including variation in bone mineral density (BMD) [9][10][11][12][13][14][15] in normal subjects, risk of developing Alzheimer's disease (AD), 16,17 and risk of developing endometrial cancer. 18 In the ERa gene (located at 6q24), variation in size of a (AT) microsatellite in the gene promoter region has been associated with variation in BMD, with alleles possessing a greater number of repeat elements being associated with increased BMD in both European 9 and Japanese 10 subjects.…”
mentioning
confidence: 99%